Incidence and Risk Factors of Tuberculosis in Patients with Human Immunodeficiency Virus Infection - Hwang, Jeong-Hwan (The Korean Academy of Medical Sciences, 2013)
Korea is a low prevalence country for human immunodeficiency virus (HIV) infection and has an intermediate tuberculosis (TB) burden. We previously reported that the incidence of TB in HIV-infected patients was 9.6 cases per 100 person-years (P-Y) between 1988 and 1997. The aims of the present study were to measure any change in incidence from the previous study, and to identify risk factors for TB in HIV-infected patients. We reviewed all medical records of HIV-infected patients who were followed-up in one tertiary hospital between 1998 and 2010. Over the total observation period of 5858.33 P-Y, TB developed in 70 patients (1.19 cases per 100 P-Y; 95% confidence interval [CI], 0.91-1.47 cases per 100 P-Y). Based on Poisson regression, one risk factor associated with TB was an initial CD4+ cell count below 200 cells/µL (relative risk, 2.34; 95% CI, 1.47-3.73). Mean CD4+ cell counts of pulmonary, extrapulmonary, and both pulmonary and extrapulmonary TB were 179.8 cells/µL, 138.3 cells/µL, and 114.2 cells/µL, respectively (P = 0.55). In conclusion, the incidence of TB in HIV-infected patients has decreased since the previous study. An initial CD4+ cell count below 200 cells/µL is an independent risk factor for development of TB in HIV-infected patients.